21. POLITIK PANGAN: HEGEMONI KOMODITAS PERTANIAN GENETICALLY MODIFIED ORGANISMS AMERIKA SERIKAT DI DUNIA TAHUN 2011-2014 - Marwan, Faiz Balya; Susiatiningsih, Hermini; Putranti, Ika Riswanti (Journal of International Relations, 2016)
Food sector particularly agricultural commodities is important for a country. Import is oneof the policy when there is food scarcity. The US is one of the importers of foodcommodities. Interesting to study US agricultural commodities given the GeneticallyModified Organisms which is still a debate about food safety. The research objective wasto determine the disclosure of US GMO agricultural commodities and whether USAIDbecame a tool of US hegemony to 41 countries in 2011-2014. This study uses the theory ofGramscian hegemony and neo-colonial dependency model Todaro and Smith withquantitative research methods. By this theory, the researchers will explain the USmeasures affecting food trade policy of developing countries. The results of this study arethe US does not do the classification of agricultural commodities. Pearson correlation testshowed strong positive correlation between the USAID Economic Development with theimport of agricultural commodities from the United States in Southeast Asia and thePacific. However, there is a significant correlation in South Asia, European non WesternEurope, the Middle East and North Africa, Sub-Saharan Africa, and Latin America and theCaribbean. Regression analysis showed two subsectors Economic Development weresignificant negative effect on imports of agricultural commodities from the US thatvariable private sector competitiveness and trade and Investment. While variableagriculture, economic opportunity, financial sector, infrastructure, and macroeconomicfoundation for growth is not significant. These findings indicate that the trade inagricultural commodities, USAID does not necessarily become a tool of US hegemony inthe country to increase imports of agricultural commodities. However, do not rule out thissubsector affect the import of commodities other than agricultural commodities.